Effects of acute postexercise chocolate milk consumption during intensive judo training on the recovery of salivary hormones, salivary SIgA, mood state, muscle soreness, and judo-related performance - Papacosta, E.; Nassis, G. P.; Gleeson, M. (Applied Physiology, Nutrition, and Metabolism, 2015)
This study examined the effects of postexercise chocolate milk (CM) or water (W) consumption during 5 days of intensive judo training with concomitant weight loss on salivary cortisol and testosterone, salivary secretory immunoglobulin A (SIgA), delayed-onset muscle soreness (DOMS), and judo-related performance. Twelve trained male judo athletes engaged in 5 days of intensive judo training followed by a simulated judo competition, on 2 separate training weeks 14 days apart. The athletes consumed 1000 mL of W (week 1) or CM (week 2) immediately post-training. During both weeks, athletes were instructed to "make weight" for the upcoming competition. Performance in timed push-ups and the Special Judo Fitness Test improved by 14.6% and 6.8%, respectively, at the end of the training week with CM consumption (both p < 0.001). Decreased salivary cortisol (p < 0.01) and a trend for an increased salivary testosterone/cortisol ratio (p = 0.07) were also observed midweek in the CM condition. Saliva flow rate was higher during the week with CM intake compared with W intake (p < 0.001). DOMS (p < 0.001) and mood disturbance (p < 0.0001) increased after the first day of training in the W condition but not in the CM condition. Salivary testosterone and SIgA responses were similar between treatments (p > 0.05). Body mass decreased by 1.9% in the W condition and by 1.1% in the CM condition, with no significant difference between treatments. This study indicates that postexercise CM consumption during short-term intensive judo training enhances aspects of recovery without affecting intentional weight loss.